The Role of Tamarix gallica Leaves Extract in Liver Injury Induced by Rifampicin Plus Isoniazid in Sprague Dawley Rats. (2nd January 2018) - Urfi, Mirza Kalam; Mujahid, Md.; , Badruddeen; Rahman, Md. Akhlaquer; Rahman, Md. Azizur
ABSTRACT: The Tamarix gallica leaves extract (TGLE) was investigated for hepatoprotective potential against rifampicin (RIF) plus isoniazid (INH)–induced liver injury in Sprague Dawley (SD) rats. All the rats of groups III and IV received 100 and 200 mg/kg body wt, respectively, of the suspension of TGLE while group V received silymarin 100 mg/kg body wt orally. After 10 min, they, along with group II, received INH plus RIF each day (50 mg/kg body wt, by mouth (PO) each) for 28 days. Group I received 10 ml/kg body wt, PO of vehicle, i.e., 1% aqueous carboxymethyl cellulose (1% CMC) throughout the study. At the end of the experiment, blood was obtained through the retro-orbital plexus under light anesthesia and the serum was separated from the sacrificed animals. A small portion of isolated liver tissue was fixed in 10% formaldehyde for histopathological examinations. The levels of elevated serum bilirubin ( p > .05– p < .05), alanine transaminase ( p > .05– p < .01), aspartate transaminase ( p > .05– p < .01), alkaline phosphatase ( p < .05– p < .01), lactate dehydrogenase ( p < .05– p < .01), and cholesterol ( p > .05– p < .01) decreased while the levels of decreased total protein ( p > .05– p < .05) and albumin ( p < .05– p < .05) increased in TGLE-treated groups III and IV as compared to group II, and the serum marker enzyme levels were toward normal, indicating protection against liver injury. It was well supported with histopathological results. Thus, Tamarix gallica leaves extract possesses promising hepatoprotective activity against RIF plus INH-induced liver injury in experimental rats.